EXPERIENCE WITH EARLY VERSUS ROUTINE ENTERIC STOMA CLOSURES: A COMPARATIVE STUDY - Shah, Nadeem Ali; Hadi, Ainul; Hussain, Mussarat; Kalim, Mohammad; Mehreen, Tahira; Shah, Inayat; Abid, Juweria (Journal of Postgraduate Medical Institute, 2016)
Objectives: To compare the outcome of enteric stoma closure within two, four and eight weeks of its formation. Methodology: A total of 283 patients with loop enteric stomas were considered for the study in the Department of Surgery, Lady Reading Hospital, Peshawar, from March 2000 to March 2005. They were divided into group A, B (intervention groups) and C (control group) in which stoma were closed at 2, 4 and 8 weeks of its formation respectively. Resection of stoma with end to end anastomosis of the gut was done in a single layer interrupted extra mucosal technique using 3/0 PDS. Results in term of successful healing or complication were recorded and analyzed. Follow up was arranged at 30th and 90th day of discharge from hospital. Results: Healing of stoma was achieved in 84.38% of patients in group A, 93.18% in group B and 95.16% in group C. Commonest complication was anastomotic leak that responded to conservative management in 3.13% of patients in Group A, 6.81% in group B and 2.42% in group C. Anastomotic leak needing re-exteriorization was found in 6.25% of patients in group A, none in group B and 1.45% in group C. There was no mortality in any of the three groups. Conclusion: Early stoma closure, preferably during the same admission is a safe, cost effective and an attractive technique.